About the Link of Monetary Policy to Household Debt, Risk in the Financial System, and Inequality - Schmidt, Jörg Holger; Justus Liebig University Giessen (My University, 2019)
Mortgage Debt and Time-Varying Monetary Policy TransmissionWe study the role of monetary policy for the dynamics of U.S. mortgage debt, which accounts for the largest part of household debt, between 1957Q1 and 2014Q3. A time-varying parameter VAR model allows us to study the variation in the mortgage debt sensitivity to monetary policy. We find that identically-sized policy shocks have lesser effects the more we move to the present. We use a DSGE model to show that a fall in the share of adjustable-rate mortgages (ARMs) could replicate this finding. Calibrating the model to the drop in the ARM share since the 1980s yields a drop in the sensitivity of housing debt to monetary policy that is quantitatively similar to the VAR results. A sacrifice ratio for mortgage debt reveals that a policy tightening directed towards reducing household debt became more expensive in terms of a loss in employment. Counterfactuals show that this result cannot be attributed to changes in monetary policy itself. The results are consistent with the mortgage rate conundrum´ found by Justiniano and have strong implications for policy.Unconventional Monetary Policy and Bank Risk-Taking in the Euro AreaThis paper studies risk-taking by European banks. After an overview of the banking landscape in the euro area, we construct a measure of risk-taking that relates changes in three-month-ahead expected credit standards for several non-financial private sector categories to the risk of the macroeconomic environment banks operate in. With this approach, we want to tackle the question if credit standards react disproportionately strong to changes in the monetary policy stance. We use an estimated bond-market-based measure to assess the overall riskiness prevailing in the economy. We want to shed some light on whether banks act excessively risky and provide new evidence as well as an alternative assessment on the amplifying nature of the risk-taking channel of monetary policy. We put our measure into a VAR model in which structural innovations are identified with sign restrictions. The key outcomes of this paper are the following. Expansionary monetary policy shocks decrease our measure of risk-taking. Decreases in our measure are caused by disproportionately strong reactions in credit standards compared to the overall macroeconomic risk, especially since the recent financial crisis. Disproportionately in the sense that our macroeconomic risk measure is less affected by expansionary monetary policy shocks than credit standards. The credit granting reaction depends on the category: In general, loans to non-financial corporations are less sensitive to monetary policy shocks while mortgages seem to be affected more. We conclude that expansionary monetary policy shifts the portfolio of banks to overall riskier asset holdings.Risk, Asset Pricing and Monetary Policy Transmission in Europe: Evidence from a Threshold-VAR ApproachThis paper investigates in how far monetary policy shocks impact European asset markets, conditional on different risk states. We distinguish between macroeconomic risk, political risk, and financial risk and separately extract three factors via principal component analysis from a set of candidate variables that are assumed to be driven by these latent types of risk. Next, these factors augment a threshold-vectorautoregressive model that contains assets and a short-rate. We illustrate that during periods of severe crisis, different risk regimes coincide. This impedes a clear delimitation among these three types of risk. Further on, impulse responses show that we indeed see state-dependency in the reaction of asset prices to monetary policy shocks. AA-rated corporate bond yields only show minor state-dependency if we distinguish between states of high and low macroeconomic or financial risk, but show very pronounced state-dependency for political risk. Their sensitivity to monetary policy shocks is highest if political risk is low. Non-investment-grade corporate bond yields as well as equity of industrial firms face the strongest state-dependency when we differentiate between macroeconomic or financial risk. If these risks are high, junk-bond yields are very sensitive to monetary policy shocks while the opposite holds for equity of industrial corporations. Interestingly, financial equity reacts positively or insignificant to hikes in short-rates. The positive reaction is most pronounced for states of high financial risk. Consequently, monetary policy transmission via distinct asset markets highly depends on the degree of these different kinds of risk inherent in European asset markets.fMoving Closer or Drifting Apart: Distributional Effects of Monetary PolicyThe heating debate about increasing income inequality forces monetary policy makers and academia to (re-)assess the nexus between (unconventional) monetary policy and inequality. We use a VAR framework to unveil the distributional effects of monetary policy and the role of redistribution in six advanced economies. While all of them experience an increase in Gini coefficients of gross income due to an expansionary monetary policy shock, only countries with relatively little redistribution display a significant response of net income inequality as well. To examine the underlying transmission channels we take a closer look at the sources of income, i.e. labor and capital income. Our findings suggest that the disproportional surge in capital income is the driving force behind the increase in net income inequality.
Über den Zusammenhang von Geldpolitik und Haushaltsverschuldung, Risiko im Finanzsystem und Ungleichheit
Keywords: ddc:330